Schizonepeta tenuifolia Briq-Saposhnikovia divaricata decoction alleviates atopic dermatitis via downregulating macrophage TRPV1 - Li, Hongmin; Liang, Jinyu; Li, Peifeng; Li, Xiangzheng; Liu, Qing; Yang, Songxue; Zhang, Chunlei; Liu, Shun; He, Yuan; Tan, Cheng (Frontiers in Pharmacology, 2024)
Objective: Schizonepeta tenuifolia -Saposhnikovia divaricata (Jingjie-Fangfeng, JF) has been used for years to treat allergic inflammatory skin diseases like atopic dermatitis, but the specific effects and mechanisms of JF are still unclear.We aim to investigate the therapeutic effect and mechanism of JF in MC903-induced atopic dermatitis-like model. Methods: JF decoction was subjected to rigorous HPLC and GC analysis. The JF decoction was then freshly prepared and administered to MC903-induced atopic dermatitis -like mice models to investigate its therapeutic effects. Our evaluation focused on several markers of inflammation including the TEWL index, ear thickness, swelling, and specific inflammation indicators such as TSLP, IL33, IgE, and immune cell presence at the lesion sites. We measured Transient Receptor Potential Vanilloid 1 (TRPV1) expression levels through immunofluorescent staining in skin tissue from both atopic dermatitis patients and the MC903-treated mice. Furthermore, TRPV1 expression and macrophage activation markers were measured in LPS/IFN-γ-stimulated Raw264.7 and THP-1 cell models in vitro. Additionally, we developed cell lines that overexpress TRPV1 and investigated how JF treatment affects NF-κB p65 phosphorylation in these cells to understand better the role of TRPV1 in atopic dermatitis.The JF decoction met the standards outlined in the Chinese pharmacopeia. The JF decoction significantly alleviated inflammatory skin symptoms and helped restore skin barrier function.Additionally, it reduced the levels of IgE and pro-inflammatory cytokines TSLP, IL-33 and IL-4. There was also a noticeable decrease in mast cell infiltration and degranulation. Notably, JF decoction reduced infiltrated macrophages with limited affection on T cell infiltration. It also decreased F4/80 + /TRPV1 + cells in atopic dermatitis mice and TRPV1 expression in LPS/IFNγ-stimulated microphages. Additionally, we observed that CD68 + /TRPV1 + cells increased in human atopic dermatitis tissue. Further studies showed that JF water extract (JF-WE) suppressed TRPV1 expression in macrophages, potentially by affecting NF-κB p65 phosphorylation rather than the JAK-STAT6 pathway.This study offers initial evidence of the effectiveness of JF-WE in suppressing inflammation in atopic dermatitis. The therapeutic effect might stems from its ability to downregulate TRPV1 expression and subsequent NF-κB p65 phosphorylation in macrophages.